Applying Some OF Freinet’s Instructional Techniques IN Our Educational Institutes - AL-Shibli, I. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Each educational system aims at having an effective way of teaching that leads to an effective learing.This needs preparing good inputs in their standard qualifications and good effective ways in the phae of processes during which reliable and valid methods and technjqucs of teaching are used. Instructional techniques have gained, lately, an increasing and great attention of educationists because of their many techniques arc Frcinet’s which they can be applied in our cducutional institution (schools, institutes and colleges),after giving a brief profile of Frcint and his educa tiona! ideas and his innovations in the field of instructional techniques.